Implementation of Greedy Algorithm for Profit and Cost Analysis of Swallow's Nest Processing Dirty to Finished Products - Efendi Efendi; Daniel Ryan Hamonangan Sitompul; Stiven Hamonangan Sinurat; Ruben Ruben; Andreas Situmorang; Dennis Jusuf Ziegel; Julfikar Rahmad; Evta Indra (Sean Institute, 2022)
Swallow's nest is made from the saliva of swallows, especially species of swallows of the genus Collocalia. Swallow's nest is used traditionally to improve health so it is widely consumed by the community. Swallow nest products are difficult to produce, causing the product to be expensive. This study aims to analyze the costs and benefits of swallow nest production. The analysis uses the Greedy algorithm, which is looking for solutions to each stage of production. The principle of Greedy's algorithm is